Pozamedyczne czynniki warunkujące wybór placówki zdrowotnej przez klientów - Bukowska-Piestrzyńska, Agnieszka (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The conditions of a free market economy make health institutions compete for patients-clients on the market. Managers should get to know extramedical factors that influence patients' decisions concerning the choice of medical services providers. This is extremely important from the point of view of functioning of these health-care institutions, especially when patients pay with their own money. The aim of this article is to: - describe extramedical factors influencing the quality of health services, - indicate the significance of marketing in everyday practice of health care institutions. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 38-45